Disparities between Adolescents with and without Disabilities in the Transition to Adulthood - Krause, Alexandra; Ueno, Koji (Disability Studies Quarterly, 2021)
Using the National Longitudinal Study of Adolescent to Adult Health (Add Health), we analyzed whether having any disability and having specific types of disabilities in adolescence were linked to the level of success in the attainment of five adulthood markers: college degree, employment, independent living, marriage, and parenthood. Using Poisson regression, we found a negative association between having a disability and the number of adulthood markers attained. However, disability type moderated this relationship: learning, intellectual, and multiple disabilities were associated with lower chances of attainment while no association was found for physical disability. Intellectual disability showed particularly strong associations. Similar results appeared when analyzing each marker separately in binary logistic regression models. Many previous studies showed disparities in these outcomes using samples that included adults of a wide age range, but the current results based on an adolescent sample show that disparities already exist in young adulthood. Current policies and programs aimed to reduce disparities between people with and without disabilities largely focus on individual efforts by people with disabilities. In light of the present results highlighting the extensive disparities, such policies should consider all key aspects of transitions and focus on institutional redesign.